2018
DOI: 10.3389/fpsyg.2018.01539
|View full text |Cite
|
Sign up to set email alerts
|

All That Glitters Is Not Grit: Three Studies of Grit in University Students

Abstract: The present research looked at the importance of the concept of grit in University students based on a mixed-method approach. Study 1 comprised 440 University students. All were given the Grit Scale, the Perceived Stress Scale, the short Warwick–Edinburgh Mental Well-being Scale, the Office of National Statistics Well-being items and the Self-Control Scale. Levels of grit were significantly higher in female students, older students and postgraduates. Grit correlated highest with self-control. Study 2 looked at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
88
2
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(137 citation statements)
references
References 54 publications
(96 reference statements)
8
88
2
7
Order By: Relevance
“…Further investigation of the influences of this concept among university students would provide deeper understanding about how it relates to productive academic outcomes. A mixed-method comprehensive project investigated grit among university students (N = 790), resulting in three studies (Kannangara et al, 2018). The quantitative studies of this project showed that gritty undergraduates had higher levels of self-control, resilience, mental well-being and were more likely to adopt a growth mindset.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation of the influences of this concept among university students would provide deeper understanding about how it relates to productive academic outcomes. A mixed-method comprehensive project investigated grit among university students (N = 790), resulting in three studies (Kannangara et al, 2018). The quantitative studies of this project showed that gritty undergraduates had higher levels of self-control, resilience, mental well-being and were more likely to adopt a growth mindset.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our study uniquely found that NCS were associated with lifestyle as characterized by homework submission This study was also the first to examine adolescent mental health in the context of NCS. While previous research has examined mental health among university students in relation to the NCS [29,30], adolescents had not yet been considered. In addition, research has indicated that grit and school satisfaction are positively associated among adolescents [12], but few studies have examined how these items relate to mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Along with academic perspectives on grit, popular media has framed these traits as essential characteristics for healthy, productive development and necessary for achieving academic success (Gray, 2016). Interestingly, research by Kannangara et al (2018) showed a correlation between grit and gender, reporting a positive relationship between grit and grade point average; only present in females. Furthermore, female students demonstrated higher levels of grit characteristics (Kannangara et al, 2018) and maintained significantly higher interest levels than males (Cross, 2014).…”
Section: Excellencementioning
confidence: 99%
“…Interestingly, research by Kannangara et al (2018) showed a correlation between grit and gender, reporting a positive relationship between grit and grade point average; only present in females. Furthermore, female students demonstrated higher levels of grit characteristics (Kannangara et al, 2018) and maintained significantly higher interest levels than males (Cross, 2014). Still, other research has found no gender differences and contend that grit was not a significant contributor to positive academic outcomes (Bazelais, Lemay & Doleck, 2016;Ivcevic, 2014;Stewart, 2015;West, 2015).…”
Section: Excellencementioning
confidence: 99%
See 1 more Smart Citation